Argentina's organic sector: issues faced by producers and consumers - Rodríguez, Elsa Mirta M. (2008)
This report presents the main results of a national project carried out during 2002-2005 entitled "The domestic and foreign potential markets of organic products in Argentina" and of other research project focused mainly on the demand. The general objectives of this work are to evaluate the marketing process of organic products and to analyze the perspectives of these markets with special attention given to the domestic market in Argentina.